Pemberian Ekstrak Methanol Daun Paliasa Menurunkan Kadar Glukosa Darah Tikus Hiperglikemik (METHANOL EXTRACT OF PALIASA LEAVES DECREASES BLOOD GLUCOSE LEVEL HYPERGLYCEMIC RATS ) - ., Yuliana; Widarsa, Tangking; Wiranatha, Gede (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
Diabetes melitus is a disease that often encountered by Indonesian people. It can cause microvascular andmacrovascular complication. Traditional herbal medicine such as paliasa (Kleinhovia hospita L.) leavesextract can decrease blood glucose. This study was aimed to identify the effectiveness of extract paliasaleaves on blood glucose decreasing for aloxan induced Wistar mice. This Control Group Design used twentyeight mice (three months old). The mice were divided randomly into four groups, i.e. control, paliasa250mg/kg body weight (BW), 500 mg/kg BW, and 750 mg/kg BW. After one week adaptation and induced byalloxan, pretest fasting blood glucose test was done. Treatment was given for two weeks and posttest bloodglucose test was done afterwards. The decrease of fasting blood glucose level was analyzed by usinganalysis of varians. Result showed there was significantly higher level of blood glucose decrease in micewith paliasa extract dose of 750mg/kgBB. Mean level of blood glucose decrease on control group was2.9±0.17, paliasa group with dose 250mg/kgBB was 29.28±1.15, paliasa 500 mg/kgBB was 46.7±2.1, danpaliasa 750mg/kgBB was 74.8±1.88.  In conclusion, extract paliasa treatment can decrease fasting bloodglucose level on hyperglycemic rats.
Keywords: diabetes melitus, blood glucose, paliasa extract, alloxan, mice